The Relationship Between Marketing Strategy and Consumer Purchase Interest: A Study of the Biofloc System of Catfish Business in Apung Village - Bara, Yuliana Ritna; Rosmayati, Siti (Yayasan Azka Hafidz Maulana, 2025)
This study aims to analyze the relationship between marketing strategies and consumer purchasing interest in the biofloc catfish farming system in Apung Village. The biofloc system is an innovative cultivation method that is more efficient in resource utilization, but this business still faces challenges in increasing consumer purchasing interest. This study used a qualitative method with a case study approach involving in-depth interviews and direct observation of business actors and consumers. The results showed that marketing strategies that include competitive pricing, promotions through social media, direct marketing to customers, and product quality assurance play a significant role in attracting consumer purchasing interest. Consumers are more interested in purchasing catfish that are marketed in an informative manner, especially if accompanied by education about the advantages of the biofloc system. In addition, prices that are in line with people's purchasing power and easy access to the product are also important factors in increasing purchasing decisions. The conclusion of this study confirms that the better the marketing strategy implemented, the higher consumer purchasing interest in the biofloc catfish farming system in Apung Village. Therefore, business actors are advised to be more active in digital marketing, maintain product quality, and improve sales services so that their businesses can grow sustainably